Efektivitas Penggunaan Media Pembelajaran Digital Video Animasi terhadap Kemampuan Menyimak dalam Pembelajaran Bahasa Indonesia Siswa Sekolah Dasar - Diandra Nofita; Cerillia Nanda Ocktaviani; Adrias Adrias; Fadila Suciana (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
Science and technology have a big influence on teachers and students in the learning process. The use of digital-based learning media is also commonly used to support the learning process. The use of animated videos in learning is one of the uses of technology in the current era, animated video media provides enormous benefits in the process of delivering learning by teachers and student learning outcomes. In learning Indonesian, learning using animated videos greatly increases students' interest in carrying out learning. In this research the author uses a library study model, by analyzing several trusted articles. This research is suitable to be used because it does not only examine it from one point of view but from several valid points of view. The aim of this study is to find out how effective the use of animated videos is on students' listening skills.